A Correlation Study of Vaginal Hygiene Behaviors and the Presence of Candida sp. in Bathroom Water with Pathological Leucorrhea in Female Students of Islamic Boarding School in Surabaya - Ratna Cahyaningtyas (JURNAL KESEHATAN LINGKUNGAN, 2019)
The health problems are frequently arise in Islamic boarding school (pesantren) such as the multiple occurrence of infectious diseases. This condition is due to poor hygiene behavior and is exacerbated by the condition of the students' dormitory environment. One of the alarming health problems in pesantren is Leuchorrea. This study aimed to investigate the correlation between vaginal hygiene behavior and the presence of Candida sp on bathroom water of Islamic Boarding School in Surabaya. This study was an observational study with cross sectional design. The study participants were 100 students selected by using simple random sampling. The correlation between vaginal hygiene behavior and Leucorrhea was analyzed by using Chi-Square Test (α=0,1). The presence of Candida in bathroom water was analyzed descriptively. The result of this study showed that 48 students (48%) were suffering from pathological leucorrhea. Vaginal hygiene behaviors associated to pathological leucorrhea were including of the frequency of changing underwear, p value = 0,014 < α(0,1); the habit of wearing underwear alternately, p value= 0,012 < α(0,01);  student's way to wash the vagina, p value= 0,001 < α(0,01), the use of tissue after washing the vagina, p value= 0,097 < α(0,01); and the frequency of changing sanitary pads, p value = 0,001 <α(0,1). Candida sp, Candida krusei, and Candida Parapsilosis were found in the bathroom water. The conclusion of this study is some of the vaginal hygiene behaviors were significantly correlated with to pathological leucorrhea, and the presence of Candida sp in bathroom water had a potential to be one of the risk factors of pathological leucorrhea of the boarding school's students.